Federal Regulatory Barriers to Grid-Deployed Energy Storage - Meyer, Andrew H. (Columbia Journal of Environmental Law, 2019)
Until recently, the most advanced form of grid-deployed energy storage involved pumping water up a hill. But “newer storage technologies like flywheels and chemical batteries have recently achieved technological maturity and are well into successful pilot stages and, in some cases, commercial operation.” If widely adopted, these new energy storage technologies will fundamentally alter the operation of our electricity system. ... Laudably, FERC has proactively addressed some particular barriers to storage, but many significant barriers remain. This Article aims to identify these barriers and offer pathways around them. Part I introduces energy storage, particularly its history, operational uses, and benefits. Part II introduces federal electricity regulation and analyzes various FERC-jurisdictional opportunities and barriers to energy storage. It also highlights recent FERC actions that proactively address or incidentally affect energy storage resources. Finally, Part III proposes actions FERC should take to remedy identified barriers. In particular, it argues that the Federal Power Act (“FPA”) requires FERC to eliminate unjust, unreasonable, and unduly discriminatory barriers to energy storage in organized wholesale markets and resource adequacy planning processes. It then argues that the Commission should clarify its policies for classifying storage devices so as to allow storage resources to perform multiple functions, thereby providing the grid with multiple benefits. Finally, it argues that energy storage resources should be considered comparably alongside traditional resources in transmission planning processes.